2018
DOI: 10.1007/s00586-018-5680-3
|View full text |Cite
|
Sign up to set email alerts
|

Pain and disability after first-time spinal fusion for lumbar degenerative disorders: a systematic review and meta-analysis

Abstract: There is a substantial improvement in pain and disability after first-time LSF for degenerative disorders. However, long-term outcomes indicate that leg pain might be more reduced and for a longer period of time than axial back pain and disability. Registration PROSPERO CRD42015026922. These slides can be retrieved under Electronic Supplementary Material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 84 publications
1
16
0
Order By: Relevance
“…In addition, while our MRSmiss patients were slightly older (44.2 vs 39.3; p = 0.047), there were no statistically significant differences in other potential confounding factors such as race, smoking, BMI, and worker's compensation status (Table 2; p > 0.08) [36][37][38][39]. Nonetheless, given our sample size is comparable to prior studies reporting pain and disability following lumbar fusion [40], our data firmly support the notion that proper level selection in fusion surgery is important, and that limitations in this regard may explain discordance between historically improving rates of technical success (e.g., radiographically confirmed fusion) and lack of proportionate gains in patient outcomes [41].…”
Section: Discussionsupporting
confidence: 54%
“…In addition, while our MRSmiss patients were slightly older (44.2 vs 39.3; p = 0.047), there were no statistically significant differences in other potential confounding factors such as race, smoking, BMI, and worker's compensation status (Table 2; p > 0.08) [36][37][38][39]. Nonetheless, given our sample size is comparable to prior studies reporting pain and disability following lumbar fusion [40], our data firmly support the notion that proper level selection in fusion surgery is important, and that limitations in this regard may explain discordance between historically improving rates of technical success (e.g., radiographically confirmed fusion) and lack of proportionate gains in patient outcomes [41].…”
Section: Discussionsupporting
confidence: 54%
“…Previous data from the Swedish National Spine Register identified that 25% of patients reported no change or worsened pain following LSFS, and at 1 year 40% of patients reported dissatisfaction regarding their outcomes [14]. Conversely, in a recent systematic review and meta-analysis of 25 prospective cohort studies (n = 1777), the clinical course of pain (both leg and back pain) and disability in patients following LSFS for degenerative disorders of the lumbar spine was analysed [15]. The results demonstrated that leg pain, back pain and disability outcomes improved significantly, immediately following LSFS (within first 4 weeks).…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that leg pain, back pain and disability outcomes improved significantly, immediately following LSFS (within first 4 weeks). Results also indicated that in the longterm (evaluation was only possible to 24 months as no data were available >24 months) leg pain outcomes might remain more reduced and for longer than back pain and disability [15].…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of the fusion surgery is established in several indications. 3,4 Some indications are more controversial: some recent studies question the need of combining fusion to decompression in degenerative spondylolisthesis, 5,6 and LSF in degenerative disc disease (DDD) is probably not reasonable in most cases. 7 The knowledge of the long-term consequences of LSF is important.…”
Section: Introductionmentioning
confidence: 99%